Avaliação consequencial do ciclo de vida: inventário do uso solo para produção prevista de biodiesel no Brasil em 2030 - Novak, Luis Henrique (2013)
Greenhouse gas emission has several negative consequences on worldwide climate. Biofuels have been considered one of the solutions to mitigate this problem by substitution of fossil fuel. However, indirect effects should be included in order to produce more reliable results in environmental assessment. In this context, Consequential Life Cycle Assessment is a method that can fill this gap. The objective of this work is to use the method to obtain the agricultural land use inventory to meet the biodiesel demand change in Brazil, considering the period 2010-2030. Only the main feedstock were included (soybean, peanut, cottonseed, palm, sunflower and canola). From these, the study found the palm oil as the marginal one. Around 5% of the potential area for palm would be used to meet the biodiesel demand change. The increased area would be 2,1 million hectares in North region of Brazil. The palm meal, which is a dependent co-product from multifunctional process, can substitute soybean meal as animal feed. The substitution avoids 0,6 million hectares of soybean in North region. Finally, the net land use inventory is 1,5 million hectares in North region of Brazil. Three alternative cenarios were developed: palm productivity unchanged, a different time horizon (2010-2020) and a different increasing rate for the determinant co-product. The same result was found for all cenarios.